When Heuristics Go Bad: Citizens’ Misevaluations of Campaign Pledge Fulfillment in Five Countries - Francois Petry; Robert Thomson; Elin Naurin; Belchior, Ana Maria; Heinz Brandenburg; Dominic Duval; Henrik Oscarsson (75th Annual MPSA Conference, 2017)
We use data from national election surveys in Canada, Great Britain, Ireland, Portugal and Sweden to clarify the impact of stereotypic political attitudes on citizens’ evaluations of specific pledge fulfillment. We start by replicating a previous analysis of the tone of evaluations in a single country, and we find that our comparative data are consistent with the findings from the previous analysis: the tone of citizens’ evaluations is positively associated with actual government performance, political knowledge, government party ID and political trust and negatively associated with opposition party ID. We also develop an original model of the accuracy of evaluations. We find that the accuracy of citizens’ evaluations is positively associated with political knowledge, but it can be negatively associated with actual government performance and with party ID and political trust in contradiction with the findings from the models for the tone of citizens’ evaluations.